Macromarketing Vol.1 A global focus marketing systems, societal development, equity and poverty - Shapiro, Stanley J.(Ed); Shultz, Clifford J. (Ed); Shapiro, Stanley J.(Ed) (Los Angeles SAGE Publications, 2009)
The domain of macromarketing